In Vitro Antiplasmodial Activity of Benzophenones and Xanthones from Edible Fruits of Garcinia Species - Lyles, James T.; Negrin, Adam; Khan, Shabana I.; He, Kan; Kennelly, Edward J. (Planta Medica, 2014)
Species of Garcinia have been used to combat malaria in traditional African and Asian medicines, including Ayurveda. In the current study, we have identified antiplasmodial benzophenone and xanthone compounds from edible Garcinia species by testing for in vitro inhibitory activity against Plasmodium falciparum. Whole fruits of Garcinia xanthochymus, G. mangostana, G. spicata, and G. livingstonei were extracted and tested for antiplasmodial activity. Garcinia xanthochymus was subjected to bioactivity-guided fractionation to identify active partitions. Purified benzophenones (1–9) and xanthones (10–18) were then screened in the plasmodial lactate dehydrogenase assay and tested for cytotoxicity against mammalian (Vero) cells. The benzophenones guttiferone E (4), isoxanthochymol (5), and guttiferone H (6), isolated from G. xanthochymus, and the xanthones α-mangostin (15), β-mangostin (16), and 3-isomangostin (17), known from G. mangostana, showed antiplasmodial activity with IC50 values in the range of 4.71–11.40 µM. Artemisinin and chloroquine were used as positive controls and exhibited IC50 values in the range of 0.01–0.24 µM. The identification of antiplasmodial benzophenone and xanthone compounds from G. xanthochymus and G. mangostana provides evidence for the antiplasmodial activity of Garcinia species and warrants further investigation of these fruits as dietary sources of chemopreventive compounds.
Keywords: Garcinia; Clusiaceae; benzophenone; xanthone; antiplasmodial activity; structure-activity relationships